Schreber's Memoirs: Myth or personal lamentation - Church, Nathan (Journal of religion and health, 1979)
Lucy Bregman's approach to Schreber'sMemoirs is scrutinized and found to be based on a number of fallacious and contradictory assumptions that call her interpretation of the book as personal religious myth into question. A social constructionist approach to mythology maintained by Berger and Luckmann is advanced, suggesting that at best Schreber's work qualifies as a quasi-mythical attempt to explain the source of his personal sociopsychic suffering. The family and interpersonal dynamics of Schreber's quasi-myth are investigated. Similarities to other cases of psychotic quasi-myths are noted and a general relationship between oppressive socialization and psychotic communications is advanced, as well as a specific alternative interpretation of Schreber's work to that proposed by Bregman.